The Role of Local Learning Media in Civics Subjects for Class V Elementary School Students - Syafruddin, Syafruddin; Sanjaya, Dewa Bagus; Suastika, I Nengah (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
This research aims to examine the role of local learning media in Civics Education (PKn) subjects for fifth grade students in elementary schools. This research uses a qualitative descriptive method with data collection techniques through observation, interviews, questionnaires and documentation. The research subjects consisted of 30 fifth grade students and one Civics teacher. The research results show that the use of local learning media, such as folklore and traditional games, increases learning motivation, understanding of the material, and student participation in the Civics learning process. As many as 85% of students felt more motivated, and 78% of students understood the material more easily when local learning media was used. In addition, students become more active in class discussions and activities. However, there are several obstacles, such as difficulties in developing teaching materials that are in accordance with local wisdom and limited time and resources. To overcome this obstacle, it is recommended that there be training for teachers and the development of adequate resources. Overall, this research confirms the importance of local learning media in improving the quality of Civics learning and provides practical recommendations for its integration in the curriculum.